Déconstruction des injonctions de genre - María Jesús Fariña Busto (Glad!)
Women’s disobedience towards cultural mandates is not a recent plan of action, nor is it from a few decades ago, even though conceptualization of this kind of disobedience can be considered recent. This article discusses the approaches taken by Latin-American women writers which are materialized in different literary genres, with a certain preference for poetry. The main objective of this paper is to present reflective and challenging wordings as well as models of resistance and rebellion. The textual corpus, which is in chronological order, corresponds to the last decades of the century not excluding, however, some references to earlier relevant texts.